2009
DOI: 10.1590/s1415-54192009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de más oclusões em crianças de 9 a 12 anos de idade da cidade de Nova Friburgo (Rio de Janeiro)

Abstract: Introduction: Knowledge of a population's epidemiological situation is important in the planning and provision of dental services. Objectives: Assess the prevalence of malocclusion in children aged 9 to 12 years old from public schools in the city of Nova Friburgo, Rio de Janeiro State, Brazil. Methods: A randomly selected sample consisting of 407 children (53.1% female) who were evaluated by a trained professional, after parental consent. Results: The most prevalent malocclusions were crowding (45.5%), excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
9
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
9
9
0
8
Order By: Relevance
“…The rate of malocclusions was similar to that of other studies evaluating children in general 13,14 . The prevalence of increased overbite in the general population of children is lower 13,14 than that in the present study; this as, therefore, the only characteristic that distinguished the group of mouth breathers.…”
Section: Discussionsupporting
confidence: 87%
“…The rate of malocclusions was similar to that of other studies evaluating children in general 13,14 . The prevalence of increased overbite in the general population of children is lower 13,14 than that in the present study; this as, therefore, the only characteristic that distinguished the group of mouth breathers.…”
Section: Discussionsupporting
confidence: 87%
“…followed by Class II malocclusion (36%) and Class III (11,7%).Still in agreement with the data obtained in this investigation, there is a study byBrito, Dias, Gleiser 20 where, knowing that the knowledge of the population's epidemiological situation is important to plan the execution of dental services in a determined population, have conducted a study with the purpose of assessing the prevalence of malocclusions in city-run school children in between 9 and 12 years of age in the city of Nova Friburgo, Rio de Janeiro. The sample was composed of 407 individuals, 191 males and 216 females who were clinically assessed by a trained professional.…”
Section: When Analyzingsupporting
confidence: 92%
“…Borges 37 mentions that excessive spacing between teeth is not commonly found in mixed dentition, except when there is a protrusion of incisors, which confirms the analysis of the present research. Deep bite was less frequent in the study sample; it was found in only 1.6% of the children examined and is in line with the findings of another study 38 . The low percentage of 0.8% of edge-to-edge bite was expected as these occlusal characteristics are more commonly found in patients with class II and III malocclusion, respectively.…”
Section: Discussionsupporting
confidence: 91%